Relationship between the Difficulty and Discrimination Indices - Hurtado Mondoñedo, Luis Leoncio (2018)
Two of the main indices used when doing a psychometric analysis of a performance test are the index of difficulty and the index of discrimination. These indices become indicators of the quality of a test as long as they are within acceptable ranges. This has two consequences, first the determination of the formula for the calculation of the indices, and secondly, the interpretation of them according to certain standards. This work shows the way how these indices are determined and related, as well as the way in which the discrimination rule influences the valuation of the test. Recommendations are also proposed for the use of both indices based on the analysis performed.